2015
DOI: 10.1111/ijs.12495
|View full text |Cite
|
Sign up to set email alerts
|

Every 15-Min Delay in Recanalization by Intra-Arterial Therapy in Acute Ischemic Stroke Increases Risk of Poor Outcome

Abstract: Longer time to recanalization was associated with poorer functional outcome post intra-arterial therapy. We recommend that a systematic approach to minimize time delay to treatment is warranted in intra-arterial therapy for acute ischemic stroke.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 26 publications
(36 reference statements)
0
19
0
Order By: Relevance
“…Time to treatment also plays a significant role: In our study, the elderly patient group had 30-min longer prehospital times and it took 45 min longer to achieve recanalization. It has been shown that time is of the essence in EVT and even minor delays can lead to worsened clinical outcome [30][31][32].…”
Section: Discussionmentioning
confidence: 99%
“…Time to treatment also plays a significant role: In our study, the elderly patient group had 30-min longer prehospital times and it took 45 min longer to achieve recanalization. It has been shown that time is of the essence in EVT and even minor delays can lead to worsened clinical outcome [30][31][32].…”
Section: Discussionmentioning
confidence: 99%
“…Benefits of ECR have now been proven in 6 randomised controlled trials, but results are time-critical [21] and it is a technically challenging procedure that is performed only in a limited number of hospitals in Australia. The advantages of a "hub-and-spoke" (or "drip-and-ship") model are having the volume to maintain experience, continue research and training and reduce the burden of after-hours service provision.…”
Section: Discussionmentioning
confidence: 99%
“…Additional specialists participating could reduce on-call frequency. A follow-the-sun model [ 26 ] where specialists in other time-zones can provide remote consultations (e.g. Australia supports UK) could limit out-of-hours disruption and support specialists’ retention.…”
Section: Discussionmentioning
confidence: 99%